The influence of the out-of-family care institutions onto child’s development - VASECHKO, LUBOVA (Journal of Education Culture and Society, 2020)
The article offers the analysis of the out-of-family care institutions and their influence on child’s development. Despite the fact that the institutional out-of-family care provides the subject with physical security and satisfies his basic needs it cannot provide the most important aspect of the development of the child - the close relationship with at least of one of the adults who would be able to captivate and become a legal guardian for several years.